Nuclear g-factors and structure of the high-spin 10+, 12+ and 7− states in isotopes 196, 198Hg - Yu. V. Nosenko; A. I. Levon; I. B. Kovgar; V. A. Onischuk; A. A. Schevchuk (Ядерна фізика та енергетика)
The integral perturbed angular distribution (IPAD) method in an external magnetic field has been used to measure the g-factors of isomers in the 196,198Hg nuclei, populated in the (α, 2n)-reaction. The results are as follows: 196Hg, g(12+ and 10+ ) = -0.19(6), g(7- ) = -0.030(17); 198Hg, g(12+ and 10+ ) = -0.18(8), g(7- ) = -0.033(14). The intrinsic structure of the isomers is discussed. Measured g-factors of 12+ and 10+ states support model “axial-symmetric oblate rotor + twoquasiparticles”. Measured g-factors of 7- states in mercury allows to confirm prediction of model “axial-symmetric rotor plus two-quasiparticles” for Hg nuclei and transient form in the platinum nuclei.